1956
DOI: 10.1172/jci103334
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Proteins of Human Synovial Fluid in Certain Disease States 1

Abstract: In search of the similarities and differences between blood plasma and synovial fluid, on one hand, and normal and pathological joint fluid on the other, it appeared important to investigate systematically the protein components of joint fluid. Investigations of the synovial fluid proteins by electrophoresis have been carried out by several authors (1-4). The identification of these proteins has been initiated (1,5). Fractionation with ammonium sulfate to obtain the albuminglobulin ratio (6) and demonstration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1959
1959
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(28 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…It has been suggested that LDL is a major plasma regulator of HeLa cell adhesion to glass (62), which is a negatively charged surface like monosodium urate crystals. In addition, there is evidence that human serum enhances the stimulation by urate crystals ofnonmitogenic synovial fibroblast responses in vitro (63,64 (19,(55)(56)(57)(58), LDL may well represent an important factor in modulation of gouty inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that LDL is a major plasma regulator of HeLa cell adhesion to glass (62), which is a negatively charged surface like monosodium urate crystals. In addition, there is evidence that human serum enhances the stimulation by urate crystals ofnonmitogenic synovial fibroblast responses in vitro (63,64 (19,(55)(56)(57)(58), LDL may well represent an important factor in modulation of gouty inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Since most synovial fluid proteins are present in plasma (19), and plasma and serum have a more constant composition than gouty synovial fluid (19,20), investigators have focused on serum and plasma effects on neutrophil-crystal interaction. Serum profoundly inhibits urate crystal-induced neutrophil lysis (18) and a serum coat has been shown by Abramson et al (7) to reduce urate crystal-induced superoxide generation.…”
Section: Introductionmentioning
confidence: 99%
“…and 20" C. The psthological joint fluids and sera were diluted before centrifugation with 0. 15 N NaCl so that a protein concentration of approximately 1.5 per cent was obtained. The enlarged tracings of the patterns revealing three or four peaks were resolved in Gaussian curves.…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of Globulin Fraaion.--Cohn's fraction I was prepared from fresh plasma according to Cohn's method as modified by Schmid, Rosa, and MacNair (11). Fraction I precipitate from 20 ml of plasma was dissolved in 10 ml of 0.055 ~ citrate pH 6.2 -4-0.05 at room temperature.…”
Section: Maleri~ls and Metkodsmentioning
confidence: 99%